Mangoes or Bananas? The quest for an authentic Asian Christian Theology - Yung, Hwa (Oxford, UK ; Irving, Calif. : Regnum, 2000, ©1997, 2010)
Biblical Theology in an Asian context
Keywords: Theology - dotrinal, Asian, contextual. Theology, Doctrinal -- Asia -- History. Missions -- Theory. Theology, Doctrinal. Asia. Theologie. Mission